Calculation of Cost of Production Using the Job Order Costing Method Against Determination of Selling Prices at PT OTO Media Kreasi - Alfian Maliki; Heru Satria Rukmana (Neraca : Jurnal Akuntansi Terapan, 2020)
PT Oto Media Kreasi is a service company engaged in the field of interior and exterior design bodies, producing based on orders or projects. The calculation of the cost of production at PT Oto Media Kreasi plays a role in determining the selling price, which affects the company's profit.The purpose of this study is to determine the calculation of the cost of production as well calculation in determining the selling price with the method applied by PT Oto Media Kreasi, also to find out the calculation of the cost of production as well as the calculation in determining the selling price using the job order costing method and to know the role of the method job order costing in loading the cost of production precisely and more efficiently.The results showed that in calculating the cost of production of PT Oto Media Kreasi still used a simple calculation, only calculating the cost of raw materials, namely Rp.1,092,778,291, direct labor costs Rp.313,200,000, and overhead costs Rp.27,600,000 . The total calculation of the company's production cost is Rp. 1,433,578,291, with a margin percentage of 35.37% of the selling price of Rp. 1,940,640,000. Whereas in calculating the cost of production using the job order costing method in calculating the cost of raw materials Rp.1,101,178,291, the accumulated residual value of raw materials Rp.8,682,000, direct labor costs Rp.313,200,000, and overhead costs Rp.60,532 .260. The total calculation of the cost of production using the job order costing method is Rp.1,466,228,551, with a margin percentage of 32.36% of the selling price of Rp.1,940,640,000. The company has not calculated the cost of goods manufactured using the job order costing method, the cost of goods manufactured is only done by estimating all costs needed to produce a product, so the costs are not classified correctly and the calculations are sufficient simple, so it is difficult to determine the right selling price for a product ordered.The proposed use of the job order costing method is expected so that the owner of the company can apply the calculation of the cost of production so that the company can determine the cost of production in determining the selling price more precisely, so that the owner can know the overall cost of producing the order and also can know the actual acquisition of margins .